Analysis of freshwater ornamental fish marketing chain in Makassar City - Lukman Daris; Asriandi; Muhammad Adam Asgar; Heriansyah (Sangia Research Media and Publishing, 2023)
Makassar City, as a marketing centre for ornamental fish in South Sulawesi, of course, has aquaculture products, especially freshwater ornamental fish, which, apart from being produced by the people in Makassar City themselves. In addition, freshwater ornamental fish are also supplied from several regions and islands in South Sulawesi, as well as outside the province of South Sulawesi. Based on this, a marketing chain and marketing strategy are needed, which are required by MSMEs, especially Ornamental Fish Businesses in Makassar City. The research method used is a case study with data collection techniques, namely surveys, to investigate various phenomena. The population in this study were freshwater ornamental fish traders in Makassar City, with a sample of 20 people, both key informants and additional informants. The study results show that the ornamental fish marketing chain system in Makassar City can start from producers/cultivators to collectors and then to diluents, and finally to consumers. The marketing strategy for ornamental fish in Makassar is seen from the marketing chain combined with the application of technology by utilizing social media in the marketing process and traditional marketing.